Case Report: Anti-NMDAR Encephalitis Presenting With Catatonic Symptoms in an Adolescent Female Patient With a History of Traumatic Exposure - Bogdan, Anamaria; Askenazy, Florence; Richelme, Christian; Gindt, Morgane; Thümmler, Susanne; Fernandez, Arnaud (Frontiers in Psychiatry, 2022)
Introduction: Catatonia is a severe syndrome associated with a high proportion of underlying organic conditions including autoimmune encephalitis. The link between catatonia and psychiatric conditions such as mood disorders and schizophrenia spectrum disorders is well established while the causative effect of Post-Traumatic Stress Disorders and stress related disorders remains speculative. Case report: Here we describe the clinical case of a 14-year-old female patient presenting to the Emergency Department of a Pediatric University Hospital with acute changes in behavior five days after a sexual abuse. Acute stress reaction was suspected. Afterwards she developed catatonic symptoms alternating from stupor to excitement, resistant to the usual treatment with benzodiazepines. The first line examinations (PE, MRI, EEG) were inconclusive. The final diagnosis of anti-NMDARE was made 22 days after her admission in a University Department of Child and Adolescent Psychiatry. Her state improved after first- and second-line immunotherapy, with no signs of relapse at this day (8 months of clinical follow-up). Discussion: The diagnosis of anti-NMDARE is challenging, involving a multidisciplinary approach. The neuropsychiatric features are complex, with no specific psychiatric phenotype. Several hypotheses are discussed to determine the role of an acute environmental stressors in the emergence of such complex neuropsychiatric clinical presentation (i.e., shared vulnerability, precipitators, consequences of preexisting psychiatric symptoms). Conclusion: Child and adolescent psychiatrists and pediatricians should be aware of the overlap between neurological and psychiatric features in the setting of anti-NMDARE. Catatonia should not be dismissed as a primary psychiatric disorder even in the context of recent traumatic exposure.